2013
DOI: 10.1002/dvdy.24018
|View full text |Cite
|
Sign up to set email alerts
|

Late‐emigrating trunk neural crest cells in turtle embryos generate an osteogenic ectomesenchyme in the plastron

Abstract: Background: The turtle plastron is composed of a keratinized epidermis overlying nine dermal bones. Its developmental origin has been controversial; recent evidence suggests that the plastral bones derive from trunk neural crest cells (NCCs). Results: This study extends the observations that there is a turtlespecific, second wave of trunk NCC delamination and migration, after the original NCCs have reached their destination and differentiated. This second wave was confirmed by immunohistochemistry in wholemoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 79 publications
(100 reference statements)
0
36
1
Order By: Relevance
“…3). This osteogenic potential is maintained in the ventral mesenchyme later in development: mesenchymal cells isolated at G19 differentiated readily into osteoblasts in cell culture (53). At this stage bone spicules begin to form (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…3). This osteogenic potential is maintained in the ventral mesenchyme later in development: mesenchymal cells isolated at G19 differentiated readily into osteoblasts in cell culture (53). At this stage bone spicules begin to form (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Several recent studies have shown turtles to be the sister group to the archosaurs (47-51), and a possible ancestral lineage has been proposed (45). The turtle plastron, its possible origin (52,53) and homologies (6,45) to skeletal elements found in other tetrapods have been studied and discussed for decades, yet this is the first study to our knowledge that has established a developmental timeline and location for plastron bone development from their early uncommitted mesenchymal condensations to the development and growth of bone extensions. This study also investigates the patterning information used in plastron bone growth.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike cranial NCCs, trunk NCCs are generally restricted from generating ectomesenchymal tissues such as bone and cartilage in vivo (Coelho-Aguiar et al, 2013). However, exceptions have been observed in turtle carapace and plastron development (Cebra-Thomas et al, 2013). NCCs from the vagal and sacral regions generate the enteric nervous system (ENS), while the cranial and sacral NCCs make important contributions to the parasympathetic nervous system.…”
Section: Neural Crest Specificationmentioning
confidence: 99%
“…; reviewed by Gross & Hanken, ), it is hypothesized that the turtle crest cells acquire the competence by losing the Hox expression of the trunk – a co‐option of skeletogenic competence from the cephalic neural crest to the trunk neural crest (Cebra‐Thomas et al. , ; Gilbert et al. ).…”
Section: Introductionmentioning
confidence: 99%